Prediction of the Principal Performance Parameters of Explosives over a Wide Range of Initial Densities - Hossein Keshavarz, Mohammad (Asian Journal of Chemistry, 2016)
New correlations are introduced for extension of Kamlet and coworkers in determining detonation velocity and the adiabatic exponent to hold loading density of explosives less than 1 g/cm3 as well as greater than 1 g/cm3. The empirical equations of Kamlet and coworkers show large per cent deviation for loading density less than 1 g/cm3; meanwhile the new correlations can be applied for CHNO explosives without any shortcoming in a wide range of loading density.